Psychosexual and psychosocial functions of anorchid young adults - Preamrudee Poomthavorn (2018)
Context: Prenatal exposure of the male fetus to androgen at wk 8-24 of gestation is essential for expression of male sex-typed behaviors in later life. Another peak of testosterone in male infants is demonstrated 1-5 months postnatally. The significance of this postnatal testosterone on male sex-typed behaviors remains to be elucidated. Bilateral congenital anorchia represents an example of an individual lacking postnatal testosterone. If postnatal testosterone surge is critical for male sex-typed behaviors, differences should be seen in this group of patients in comparison with men with functioning testes. Objective: The objective of the study was to examine the psychosexual function of males with anorchia. Design: This was a cross-sectional study. Setting: The study was conducted at the Royal Children's Hospital, Melbourne, Australia, a referral center. Patients and Interventions: Fifteen young male adults with anorchia and 15 healthy young males were enrolled in the study. All of them completed the same set of questionnaires evaluating general health and psychological health as well as sexuality. All had androgen replacement treatment to induce puberty and maintain adult androgen effect. Main Outcome Measures: General health, psychosocial, and psychosexual functionings according to the validated questionnaires were measured. Results: There were no differences in age, education, marital status, and identified gender between subjects and controls. No significant differences of general health, psychosocial, and psychosexual functionings of the subjects with anorchia and healthy young adults were demonstrated. Conclusion: A postnatal testosterone surge does not seem to be critical for male-typed sexual behaviors in men with anorchia when adolescent testosterone replacement has occurred. Copyright © 2009 by The Endocrine Society.